2006
DOI: 10.1159/000095609
|View full text |Cite
|
Sign up to set email alerts
|

A Frequency-Position Function for the Human Cochlear Spiral Ganglion

Abstract: Greenwood’s frequency-position function for the organ of Corti (OC) is commonly used to estimate represented frequencies for cochlear implant (CI) electrodes, both in temporal bone studies and in imaging studies of living CI recipients. However, many contemporary CIs position stimulating electrodes near the modiolus, directly targeting the spiral ganglion (SG) cells within Rosenthal’s canal. At the extreme base and apex, the SG does not extend as far as the OC, and the radial nerve fibers take a tangential cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 16 publications
5
54
0
Order By: Relevance
“…Because it is logical to assume that our normalized data should cover the region from 0 to 100% of both the OC and SG, that polynomial function was constrained to begin at the point x = 0, y = 0, to end at x = 100, y = 100, and to be monotonic (Sridhar et al 2006). The addition of two more cochlear specimens to the data set did not eliminate a systematic bias observed near the base (up to 20%) for the thirdorder polynomial, so the final set of data in this report was fit by a different mathematical function:…”
Section: Sg Frequency-position Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it is logical to assume that our normalized data should cover the region from 0 to 100% of both the OC and SG, that polynomial function was constrained to begin at the point x = 0, y = 0, to end at x = 100, y = 100, and to be monotonic (Sridhar et al 2006). The addition of two more cochlear specimens to the data set did not eliminate a systematic bias observed near the base (up to 20%) for the thirdorder polynomial, so the final set of data in this report was fit by a different mathematical function:…”
Section: Sg Frequency-position Functionmentioning
confidence: 99%
“…Some preliminary data on the frequency-position map for the SG from a subset of the cochlear specimens included in this study were reported previously in the proceedings of the First International Electro-Acoustic Workshop (Sridhar et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To express the frequency-position function of a normal ear versus angles, we used the reconstruction work of Kawano et al (1996, Table 2), where they listed angles (-) versus percentage lengths of the organ of Corti. We also drew the frequency-position function that could result from the excitation of the spiral ganglion cells (hairline), using the function modeling the projection of fibers from the organ of Corti to the spiral ganglion as described by Sridhar et al (2005) and using again the reconstruction work of Kawano et al to assign angles to percentages of the length of the spiral ganglion. The frequencies of acoustic stimuli at match were again lower than estimated by the frequency position function of a normal ear.…”
Section: Pitch Comparisonsmentioning
confidence: 99%
“…However, hair cells are usually absent in implant patients after conventional implant surgery. The remaining neural targets, dendrites and cell bodies in the spiral ganglion, do not have the same relationship to distance along the cochlear partition as hair cells (Kawano et al 1996;Sridhar et al 2006). Thus, the Greenwood frequency-place (or frequency to distance along the cochlea) map is not likely to be appropriate for cochlear implant patients.…”
mentioning
confidence: 99%